The influence of relationship marketing on customer loyalty: Customer satisfaction as a mediation variable - Darmayasa, Gusti Ngurah Ary Raka; Yasa, Ni Nyoman Kerti (International research journal of management, IT and social sciences, 2021)
This study aims to examine and explain the effect of relationship marketing on customer loyalty mediated by customer satisfaction. To achieve the research objectives, data analysis using Path Analysis and Sobel Test. Sampling by non-probability sampling with purposive sampling method and the size of the sample taken is 120 respondents. The results of the analysis show that relationship marketing has a positive and significant effect on customer loyalty at Livingstone Café & Bakery Seminyak Bali. Furthermore, relationship marketing also has a positive and significant effect on customer satisfaction at Livingstone Café & Bakery Seminyak Bali. Customer satisfaction has a positive and significant effect on customer loyalty at Livingstone Café & Bakery Seminyak Bali and customer satisfaction can significantly mediate the effect of relationship marketing on customer loyalty at Livingstone Cafe & Bakery Seminyak Bali. Suggestions that can be recommended to the management of Livingstone Café & Bakery Seminyak Bali are to always build better relationship marketing to increase customer satisfaction and customer loyalty.